2017
DOI: 10.1097/dad.0000000000000587
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Assessment of Lichenoid Dermatitis Observed in Patients With Advanced Malignancies on Antiprogramed Cell Death–1 (anti–PD-1) Therapy With or Without Ipilimumab

Abstract: Lichenoid drug reaction is a common adverse reaction in patients taking immune-modulatory agents such as antiprogramed cell death (PD-1) and cytotoxic T lymphocyte antigen-4 agents. The authors describe the clinical and histologic features of lichenoid drug reaction in 20 biopsies from 15 patients on anti-PD-1 agents and 9 biopsies from 7 patients on anti-PD-1 plus ipilimumab therapy. Clinically, all except 2 patients presented with discrete, violaceous exanthematous papules to plaques. The lichenoid inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 16 publications
1
27
0
Order By: Relevance
“…Histopathology findings (n=4) showed patchy-to-florid lichenoid interface dermatitis in the upper lamina propria, with variable degrees of basal vacuolar changes and apoptosis. Of note, and as previously reported in patients developing cutaneous lichenoid reactions with anti-PD-1, 8 more atypical features such as hypergranulosis and marked parakeratosis were also observed. Ancillary immunostaining demonstrated that the band-like T-cell infiltrate was predominantly CD4/CD8-positive (1:1).…”
supporting
confidence: 84%
See 2 more Smart Citations
“…Histopathology findings (n=4) showed patchy-to-florid lichenoid interface dermatitis in the upper lamina propria, with variable degrees of basal vacuolar changes and apoptosis. Of note, and as previously reported in patients developing cutaneous lichenoid reactions with anti-PD-1, 8 more atypical features such as hypergranulosis and marked parakeratosis were also observed. Ancillary immunostaining demonstrated that the band-like T-cell infiltrate was predominantly CD4/CD8-positive (1:1).…”
supporting
confidence: 84%
“…47 In contrast, sparing of oral mucous membranes is often reported and oral lichenoid reactions (OLR) have only been anecdotally described. 48 Herein, we describe the clinicopathological features of 10 new cases in Table 1. To our knowledge, this is the largest series of patients developing OLRs with immune checkpoint antibodies reported to date.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Skin rash is one of the most common immune‐related adverse events seen in patients treated with either anti‐CTLA4 or anti‐PD‐1 therapies and can limit therapeutic efficacy because the dose may need to be decreased or treatment halted because of the severity of the cutaneous eruption . Specifically, lichenoid drug rash is a common adverse reaction in patients on PD‐1 inhibitors . Mid‐ to high‐potency topical corticosteroids and systemic antihistamines are first‐line treatments of grade 1 and 2 skin toxicities associated with PD‐1 inhibitor therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Dermatologic toxicities are one of the most frequent immunerelated adverse events (irAEs) induced by these new monoclonal antibodies. [4][5][6][7][8] Herein, we describe the clinicopathological features of 10 new cases in Table 1. vitiligo, alopecia areata and bullous pemphigoid) are amongst the most commonly reported AEs.…”
Section: Editormentioning
confidence: 99%